2022
DOI: 10.1002/pssb.202100666
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Optical Properties of the Type‐II GaN/SiH van der Waals Heterostructure: A First‐Principles Study

Abstract: In recent years, constructing van der Waals (vdW) heterostructures based on different 2D materials has been a highly effective way to obtain desired electronic and optical properties. Herein, on the basis of first‐principles calculations, a 2D vdW heterostructure is constructed by vertically stacking the indirect‐bandgap gallium nitride (GaN) and silicane (SiH) monolayers. For the formed heterostructure, the structural, electronic, and optical properties are all computed. The obtained results show that the het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This interlayer separation is consistent with that in other SiH-based heterostructures. 41,51,52 Moreover, to check the stability of the GR/SiH heterostructure, the binding energy is calculated as E b = [ E GR/SiH − E GR − E SiH ]/ A , where E GR/SiH , E GR and E SiH are the total energies of the GR/SiH heterostructure, isolated GR and SiH monolayers, respectively. A is the surface area of the heterostructure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This interlayer separation is consistent with that in other SiH-based heterostructures. 41,51,52 Moreover, to check the stability of the GR/SiH heterostructure, the binding energy is calculated as E b = [ E GR/SiH − E GR − E SiH ]/ A , where E GR/SiH , E GR and E SiH are the total energies of the GR/SiH heterostructure, isolated GR and SiH monolayers, respectively. A is the surface area of the heterostructure.…”
Section: Resultsmentioning
confidence: 99%
“…This interlayer separation is consistent with that in other SiH-based heterostructures. 41,51,52 Moreover, to check the stability of the GR/SiH heterostructure, the binding energy is calculated as…”
Section: Resultsmentioning
confidence: 99%
“… 49 This exploration seeks to investigate the viability of SiH-based hetero-junctions for photocatalytic applications. Rese-arch has also revealed that a GaN/SiH vdW heterostructure has an increased optical absorption rate compared to a GaN mono-layer, 50 reaching a peak of 21.6% in the UV region. Furthermore, an AlAs/SiH vdW heterostructure exhibits an impressive high optical absorption coefficient in the visible light region, measuring 2.2 × 10 5 cm −1 .…”
Section: Introductionmentioning
confidence: 99%